Analysis of Community Intentions on Islamic Bank Products Using The Theory of Planned Behavior Approach - Nonie Afrianti Afrianti (Islamic Economics Journal, 2022)
This study aims to determine the effect of attitudes on behavior, perceived behavioral control, and subjective norms or to know perceptions and understandings and then develop into the intentions of Bengkulu city panoramic market traders in behaving using Islamic bank products. The sampling technique used is the theory of Hair obtained a sample of 230 respondents with the sampling technique used is accidental sampling. The analysis technique used Structural Equation Modeling (SEM) with the SmartPLS 3 tool. The results of this study indicate that the variables of attitude towards behavior, perceived behavioral control and subjective norms have a significant effect on intentions and intentions have a significant effect on the behavior of a trader at the Bengkulu city panorama market in behaving in using Islamic bank products.